2008
DOI: 10.1177/1073191107307966
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Adolescent Risk Assessment Instruments

Abstract: ResumenEl presente trabajo tiene como finalidad determinar la utilidad del Inventario de Gestión e Intervención para Jóvenes (IGI-J), que se emplea tanto en la predicción de la conducta delictiva reiterada en jóvenes infractores, como en la implementación de programas de intervención apropiados para dicha población. Se realizó un estudio retrospectivo con una muestra de 258 delincuentes juveniles que se hallaban cumpliendo una medida judicial. El instrumento que evaluó la predicción de la reincidencia es el Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
120
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(145 citation statements)
references
References 51 publications
16
120
3
6
Order By: Relevance
“…There were a large number of studies that met the first three criteria, but combined males and females when calculating the predictive validity of the YLS/CMI (Campbell, 2009;Catchepole & Gretton, 2003;Clarke, 2015;Cuervo & Villanueva, 2014;Guebert & Olver, 2014;Hilterman, Nicholls, & Nieuwenhuizen, 2013;Li, Chu, Goh, Ng, & Zeng, 2015;Livsey, 2005;Onifade, Barnes, Campbell, Anderson, Petersen, & Davidson, 2014;Onifade, Davidson, Livsey, Turke, Horton, Malinowski, Atkinson, & Wimberly, 2008;Onifade, Wilkins, Davidson, Campbell, & Petersen, 2011;Thompson & Pope, 2005;Peterson-Badali, Skilling, & Haquanee, 2015;Shepherd, Green, & Omobien, 2005;Shepherd, Singh, & Fullam, 2015;Upperton & Thompson, 2007;Vieira, Skilling, & Peterson-Badali, 2009;Welsh, Schmidt, McKinnon, Chattha, & Meyers, 2008). Since the research question addresses gender differences, these studies that did not separate males and females were excluded from the meta-analyses.…”
Section: Methods For Locating Studiesmentioning
confidence: 99%
“…There were a large number of studies that met the first three criteria, but combined males and females when calculating the predictive validity of the YLS/CMI (Campbell, 2009;Catchepole & Gretton, 2003;Clarke, 2015;Cuervo & Villanueva, 2014;Guebert & Olver, 2014;Hilterman, Nicholls, & Nieuwenhuizen, 2013;Li, Chu, Goh, Ng, & Zeng, 2015;Livsey, 2005;Onifade, Barnes, Campbell, Anderson, Petersen, & Davidson, 2014;Onifade, Davidson, Livsey, Turke, Horton, Malinowski, Atkinson, & Wimberly, 2008;Onifade, Wilkins, Davidson, Campbell, & Petersen, 2011;Thompson & Pope, 2005;Peterson-Badali, Skilling, & Haquanee, 2015;Shepherd, Green, & Omobien, 2005;Shepherd, Singh, & Fullam, 2015;Upperton & Thompson, 2007;Vieira, Skilling, & Peterson-Badali, 2009;Welsh, Schmidt, McKinnon, Chattha, & Meyers, 2008). Since the research question addresses gender differences, these studies that did not separate males and females were excluded from the meta-analyses.…”
Section: Methods For Locating Studiesmentioning
confidence: 99%
“…Two recent studies found that among incarcerated adolescent females PCL:YV scores were not predictive of future offending [52,77]. The study of Welsh et al [82] examined the predictive and incremental validity in a male and female adolescent sample of three instruments used in youth risk assessments: The structured assessment of violence risk in youth (SAVRY) offered the most incremental predictive validity for general recidivism and violent recidivism whereas the PCL:YV followed closely behind.…”
Section: J Psychopathy Across Gendermentioning
confidence: 99%
“…In terms of predictive validity, the SAVRY has been shown to significantly predict both general and violent recidivism (Catchpole & Gretton, 2003;Dolan & Rennie, 2008). Welsh, Schmidt, McKinnon, Chattha, and Meyers (2008) found that in a sample of juvenile offenders the SAVRY was able to predict both general and violent reoffending above and beyond that of the Psychopathy Checklist: Youth Version (PCL-YV; Forth, Kosson, & Hare, 2003) and the Youth Level of Service/Case Management Inventory (YLS/CMI; Hoge, Andrews, & Leschied, 2002). In addition, the SAVRY has also been found to significantly predict physical violence, rule violations and verbal threats in a sample of youth in residential treatment (Lodewijks, Doreleijers, de Ruiter, & Borum, 2008).…”
Section: The Structured Assessment Of Violence Risk In Youth (Savry)mentioning
confidence: 99%